IN VITRO culture establishment from hypocotyl and cotyledon explants of two Bangladeshi sunflower (Helianthus annuus L. ) varieties - Oshin, Afsana Tasnim (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.